1962
DOI: 10.1104/pp.37.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Chelated Iron by Soybean Roots in Nutrient Solutions

Abstract: During the past decade, many investigators have studied the uptake of micronutrients when supplied as chelates to plant roots. Considerable controversy has arisen as to whether the metal is dissociated from the organic ligand at the root membrane and is taken up by itself, or whether the entire chelate is absorbed through the root nmembrane. Several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In an earlier study on soybean plants grown in nutrient solution, it was reported that the chelating agent was absorbed by plants only when the chelating agent concentration was higher than the metal ion concentration [9]. It was also concluded that chelating agents applied in the absence of iron are absorbed by the plant and bound to the iron in the plant, causing chlorosis [9]. Spraying such plants with FeSO 4 resulted in rapid recovery and chlorosis elimination [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an earlier study on soybean plants grown in nutrient solution, it was reported that the chelating agent was absorbed by plants only when the chelating agent concentration was higher than the metal ion concentration [9]. It was also concluded that chelating agents applied in the absence of iron are absorbed by the plant and bound to the iron in the plant, causing chlorosis [9]. Spraying such plants with FeSO 4 resulted in rapid recovery and chlorosis elimination [9].…”
Section: Discussionmentioning
confidence: 99%
“…It was also concluded that chelating agents applied in the absence of iron are absorbed by the plant and bound to the iron in the plant, causing chlorosis [9]. Spraying such plants with FeSO 4 resulted in rapid recovery and chlorosis elimination [9]. It was also reported that in nutrient solutions of chelating agent and ferric ion, the roots of kidney beans and soybeans seeds competed with the chelating agents for the ferric ion, and the competitive effect was overcome by adding more metal ion into the nutrient solution [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of Zn, Mn and B was also reported to increase yield, improving seed quality, and oil [13] [14]. Other studies have also reported that iron-chlorosis symptoms of soybean plants can be reduced by adding a chelating agent with Fe in Hoagland solutions [15] [16]. Although soil contains all nutrients, under certain conditions, these nutrients, especially the cations, can be tightly bound to the soil and also precipitation can limit their availability to the crop.…”
Section: Introductionmentioning
confidence: 99%